Constructed wetlands combined with UV disinfection systems for removal of enteric pathogens and wastewater contaminants. - Azaizeh, H.
Water shortage is an ongoing cardinal issue in the Middle East region. Wastewater reuse offers some remediation, but to-date many rural communities in the Palestinian Authority (PA) and in Jordan are not connected to centralized wastewater treatment plants (WWTPs), many of them are disposing of their wastewater using infiltration septic tanks. This highlights the need for a small, local, low cost WWTP that can directly benefit local communities, producing effluents suitable for unrestricted irrigation. Constructed wetlands (CWs) could offer a solution as they are relatively easy and cheap to construct and maintain, and effective in removal of many pollutants. Nevertheless, pathogen removal in CWs is often not adequate, calling for additional disinfection. Here we describe the use of low-cost, consumer level, UV based disinfection systems coupled to CWs for wastewater treatment in three CWs: in Israel, Jordan and in the PA. Once mature, our adapted CWs reduced chemical oxygen demand (COD) load, and, given proper use of the UV systems, inactivated indicator bacteria (faecal and E. coli) to levels suitable for irrigation, even when UV transmission (UVT) levels were low (∼40%). Our results demonstrate the promise in this combined treatment technique for cheap and simple wastewater treatment suitable for the Middle East region.
Keywords: COD removal; Constructed wetlands; Pathogen removal; Small communities; UV disinfection; Wetland plants